RESISTANCE STATUS AND MECHANISM OF Aedes aegypti AGAINST THREE CLASSES OF INSECTICIDES IN SALATIGA CITY, INDONESIA (Proceedings of the International Conference on Public Health, 2022)
Insecticide resistance is a major problem in dengue vector control in Indonesia. SalatigaCity, one of Central Java's dengue-endemic areas, has been using insecticide for vectorcontrol for decades. To select the insecticide used, it is necessary to understand the statusand mechanism of resistance to various insecticides. This study aimed to determine thestatus and mechanism of Aedes aegypti resistance in Salatiga City. This study used adescriptive method. Larvae were collected from 8 endemic villages in Salatiga City. Thelarvae were then reared to produce adult mosquitoes. A resistance test was conductedusing the WHO-Impregnated paper method on F1 mosquitoes. The insecticides used forthe test were malathion 5%, phenytotrione 1% (Organophosphate); Bendiocarb 0.1%,Propoxur 0.1% (Carbamate); Lambda Cyhalothrin 0.03%, Deltamethrin 0.05%,Permethrin 0.25%, and Cypermethrin 0.05.% (Pyretrhoid). To determine the resistancemechanism of the target site mutation, sequencing of the Domain II VGSC and ACE1genes was carried out. The test results showed that Ae. aegypti from 8 locations wereresistant to all insecticides. The highest mortality after 24 hours observation was onorganophosphate group. Molecular tests showed that Single Nucleotide Polymorphism hadoccurred in the S989P and V1016G alleles of the VGSC gene, indicating molecularresistance to Pyretrhoid insecticides. The ACE1 gene sequences showed no mutations inthe G119S allele, indicating the possibility of metabolic resistance to organophosphatesand carbamates. In case of a dengue outbreak, it is recommended to use organophosphatebecause it has the highest percentage of mosquito mortality, and only metabolic resistanceoccurs without target site mutations.
Keywords: Resistance; Aedes aegypti; Salatiga; Insecticide